Analysis of changes in the official exchange rate and its impact on the general budget for the period (2003-2021) - Shakir, Atyaf; ALemara, Shaban (The Gulf Economist, 2023)
The study aims to track the course of changes made by the monetary authority in the exchange rate from 2003 until 2021, which had a direct or indirect impact on the general budget. The monetary authority took a different measure that reduces the exchange rate of the Iraqi dinar against the US dollar. In reaching the goal, the study adopted the inductive approach, using the descriptive and statistical methods in economic analysis. The study concluded that the changes that occurred towards raising the exchange rate of the dinar against the dollar were aimed at using the exchange rate as a target. As a mediator for the purpose of achieving the goal related to the stability of the general level of prices and reducing inflation rates, while the change that occurred at the end of the study, i.e. the year 2020, was aimed at strengthening the state’s resources from its main source, which is crude oil, to cover its increasing expenditures in the general budget, and it succeeded to a large extent in that, but it At the same time, it caused great damage to the real income levels of individuals, especially those with limited and low incomes, as a large segment of individuals entered below the poverty line. Then the study put forward proposals about the process of the official change of exchange represented in that this change be carefully studied so that the effects of it are taken into account so that its positive effects outweigh its negative effects.